Species‐rich semi‐natural grasslands have a higher resistance but a lower resilience than intensively managed agricultural grasslands in response to climate anomalies. Issue 2 (11th January 2016) - De Keersmaecker, Wanda; van Rooijen, Nils; Lhermitte, Stef; Tits, Laurent; Schaminée, Joop; Coppin, Pol; Honnay, Olivier; Somers, Ben
Summary: The stable delivery of ecosystem services provided by grasslands is strongly dependent on the stability of grassland ecosystem functions such as biomass production. Biomass production is in turn strongly affected by the frequency and intensity of climate extremes. The aim of this study is to evaluate to what extent species‐poor intensively managed agricultural grasslands can maintain their biomass productivity under climate anomalies, as compared to species‐rich, semi‐natural grasslands. Our hypothesis is that species richness stabilizes biomass production over time. Biomass production stability was assessed in response to drought and temperature anomalies using 14 years of the Normalized Difference Vegetation Index (NDVI), temperature and drought index time series. More specifically, vegetation resistance (i.e. the ability to withstand the climate anomaly) and resilience (i.e. the recovery rate) were derived using an auto‐regressive model with external input variables (ARx). The stability metrics for both grasslands were subsequently compared. We found that semi‐natural grasslands exhibited a higher resistance but lower resilience than agricultural grasslands in the Netherlands. Furthermore, the difference in stability between semi‐natural and agricultural grasslands was dependent on the physical geography: the most significant differences in resistance were observed in coastal dunes and riverine areas, whereas the differences in resilience were the most significant in coastal dunes and fens. Synthesis and applications . We conclude that semi‐natural grasslands show a higher resistance to drought and temperature anomalies compared to agricultural grasslands. These results underline the need to reassess the ways agricultural practices are performed. More specifically, increasing the plant species richness of agricultural grasslands and lowering their mowing and grazing frequency may contribute to buffer their biomass production stability against climate extremes. Abstract : We conclude that semi‐natural grasslands show a higher resistance to drought and temperature anomalies compared to agricultural grasslands. These results underline the need to reassess the ways agricultural practices are performed. More specifically, increasing the plant species richness of agricultural grasslands and lowering their mowing and grazing frequency may contribute to buffer their biomass production stability against climate extremes.